Sex differences in the associations between maternal prenatal distress and infant cortisol reactivity and recovery - Kortesluoma Susanna; Korhonen Laura; Pelto Juho; Hyttinen Sirpa; Laine Olli; Karlsson Linnea; Karlsson Hasse (Elsevier, 2022)
Previous research suggests that maternal prenatal psychological distress (PPD) is related to altered cortisol reactivity in the exposed child. There are indications for the sex differences in vulnerability for prenatal adversities that depend on the exposure and child outcome. Still, it is not known whether the association between maternal PPD and infant cortisol stress response is moderated by sex. In addition, the recovery phase of the cortisol stress response has not been given as much attention as reactivity. Our aim was to study the sex differences in the associations between self-reported maternal prenatal depressive-, anxiety- and pregnancy-related anxiety symptoms through gestational weeks 14, 24 and 34 and the saliva cortisol reactivity to and recovery from the acute stress among 10-week-old infants. The study population comprised of 363 mother-infant pairs from the FinnBrain Birth Cohort Study. We found evidence for sex-dependent associations between PPD exposure and infant cortisol response. A less steep recovery slope (-10 % per one SD increase in PPD [95 % CI = -18 to -2 %] and -8 % [-16 to 0 %] depending on the exposure) and a possibly less steep reactivity slope (-14 % [95 % CI = -25 to 0 %] and -10 % [-21 to 3 %]) were associated with higher PPD exposure in females. Of the PPD measures, the strongly intercorrelated, and thus combined, depressive and anxiety symptom score provided the most robust prediction of infant cortisol recovery. Our results demonstrate sexually dimorphic alterations in the functioning of the infant hypothalamus-pituitary-adrenal axis and especially in the functioning of the negative feedback loop of the axis after prenatal PPD exposure among healthy babies.